Income and Employment Effects of Health Shocks - A Test Case for the German Welfare State - Riphahn, Regina Therese (Journal of Population Economics, 1999)
Using data from the first eleven waves of the German Socio-Economic Panel this study investigates the dynamic effects of health shocks on employment and economic well-being of older workers. A health shock trebles the probability of leaving the labor force and almost doubles the unemployment risk. The financial effects of health shocks are small on average and those individuals with the highest remaining earnings potential are least affected by the health shock. Welfare state instruments support the poorest section of the population but do not succeed in neutralizing the effects of a health shock for these group
WiSo-Import:2015-03-26:2674
Keywords: Health; Labor force participation; Welfare state